Concentrations of Fluoride in Drinking Water and Tea Samples and Associations with Dental Fluorosis - Afzal, Sadaf; Durrani, Salma; Malghani, Ayesha Khan; Khan, Maria; Sajjad, Naheed; Tariq, Nabeela (Pakistan Journal of Nutrition, 2015)
Water and tea are the main sources of fluoride intake in humans and may cause dental fluorosis during tooth development. The current study aimed to determine the fluoride concentrations in drinking water and tea samples and their association with dental fluorosis. To evaluate the prevalence of dental fluorosis, 882 primary school children (8-13 years) were analyzed and 14% were found to be affected. Drinking water samples (34) were analyzed and the fluoride concentrations ranged from 0.61 to 2.55 ppm. Fourteen (14) different branded and unbranded tea leaf samples exhibited fluoride concentrations of 5.73-7.70 and 2.13-4.56 ppm, respectively, based on the ion-selective electrode method. It was concluded that the dental fluorosis observed among school children was directly associated with the fluoride concentrations in their drinking water and tea samples.